2022
DOI: 10.1111/cpr.13293
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells‐based therapy for the oviduct injury via immunomodulation and angiogenesis in vivo

Abstract: Objectives: As a result of the current limitation of therapeutic strategies, the repair and regeneration of oviduct injuries required an alternative treatment. We present a novel approach to treat oviduct injuries through a dental pulp stem cells (DPSCs)based therapy.Materials and Methods: In vitro and in vivo models have been established. Immunofluorescence staining, flow cytometry and enzyme-linked immunosorbent assay (ELISA) analysis were used to investigate the features and angiogenic properties of DPSCs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…There are some reports suggested that IL-1β blockade may be a preventive strategy for high risk individuals [44]. In our previous study, we found that both DPSC and DPSC lysate could signi cantly inhibit the expression of IL-1β [29,45]. This may be one of the mechanisms by which DPSC lysate inhibits tumor.…”
Section: Discussionmentioning
confidence: 70%
“…There are some reports suggested that IL-1β blockade may be a preventive strategy for high risk individuals [44]. In our previous study, we found that both DPSC and DPSC lysate could signi cantly inhibit the expression of IL-1β [29,45]. This may be one of the mechanisms by which DPSC lysate inhibits tumor.…”
Section: Discussionmentioning
confidence: 70%
“…The anti-proliferative and pro-apoptotic effects of EVSs derived from UMSC were detected in bladder carcinoma [ 45 ].There are some reports suggested that IL-1β blockade may be a preventive strategy for high risk individuals [ 46 ]. In our previous study, we found that both DPSC and DPSC lysate could significantly inhibit the expression of IL-1β [ 19 , 47 ]. This may be one of the mechanisms by which DPSC lysate inhibits tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Dental pulp stem cells (DPSCs) possess mesenchymal stem cell–like properties and have advantages such as source-abundant, readily available, ethically uncontroversial, and low-immunogenicity characteristics. 6 , 7 , 8 As for experiments in dental pulp regeneration in vivo, some studies have shown that DPSCs were able to differentiate into odontoblastlike and endotheliumlike cells to reconstruct the structure of the pulp-dentin complex. 9 , 10 , 11 In addition, DPSCs had the ability to proliferate rapidly and maintain a good stemness, even if the culture medium without the addition of animal serum or exogenous growth factors in vitro.…”
Section: Introductionmentioning
confidence: 99%